2022
DOI: 10.1371/journal.pone.0263443
|View full text |Cite
|
Sign up to set email alerts
|

sFlt-1/PlGF ratio for prediction of preeclampsia in clinical routine: A pragmatic real-world analysis of healthcare resource utilisation

Abstract: Background We investigated the impact of the soluble fms-like tyrosine kinase 1 (sFlt-1)/placental growth factor (PlGF) ratio to predict short-term risk of preeclampsia on clinical utility and healthcare resource utilisation using real-world data (RWD), and compared findings with health economic modelling from previous studies. Methods and findings This retrospective analysis compared data from the German population of a multicentre clinical study (PROGNOSIS, n = 203; sFlt-1/PlGF ratio blinded and unavailabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The first data confirming the hypotheses about the imbalance of angiogenic and antiangiogenic proteins in pre-eclampsia patients were collected when Levine et al (2004) found that, in pre-eclampsia, the levels of sFlt-1 increased while those of PlGF decreased [ 14 ]. In the following few years, these data have been repeatedly confirmed [ 7 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Sflt1/plgf Ratiomentioning
confidence: 80%
“…The first data confirming the hypotheses about the imbalance of angiogenic and antiangiogenic proteins in pre-eclampsia patients were collected when Levine et al (2004) found that, in pre-eclampsia, the levels of sFlt-1 increased while those of PlGF decreased [ 14 ]. In the following few years, these data have been repeatedly confirmed [ 7 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Sflt1/plgf Ratiomentioning
confidence: 80%
“…The most widely used clinical predictor of the development of PE in current clinical practice is the sFLT1/PlGF ratio of above 38 52 . However, depending on the demographic profile tested, even though the predictive value for the development of PE in the following week is very good (99.3%), this value drops significantly for the prediction in the next 4 weeks (36.7% with 66.2% sensitivity and 83.1% specificity) 53 .…”
Section: Discussionmentioning
confidence: 99%
“…The sFlt-1 to PlGF ratio is increased in pregnant women before the onset of PE with an elevated ratio suggestive of PE, whereas the diagnosis of PE can be ruled out within 1 week for low ratios. [218][219][220][221][222] The search for potential biomarkers for PE yielded no definite markers to predict the disease's onset. Close real-time monitoring of maternal and fetal status and vital parameters is the key before labor onset.…”
Section: Diagnostic and Therapeutic Strategies In Pementioning
confidence: 99%
“…There are not too many confirmatory, reliable screening or diagnostic tests for PE that could conclusively diagnose this condition with certainty. The sFlt‐1 to PlGF ratio is increased in pregnant women before the onset of PE with an elevated ratio suggestive of PE, whereas the diagnosis of PE can be ruled out within 1 week for low ratios 218–222 . The search for potential biomarkers for PE yielded no definite markers to predict the disease's onset.…”
Section: Diagnostic and Therapeutic Strategies In Pementioning
confidence: 99%